Heteroepitaxial Growth of GaN on Unconventional Templates and Layer‐Transfer Techniques for Large‐Area, Flexible/Stretchable Light‐Emitting Diodes. Issue 4 (20th December 2015) - Choi, Jun Hee; Kim, Jinwoo; Yoo, Hyobin; Liu, Jinyun; Kim, Sunil; Baik, Chan‐Wook; Cho, Chae‐Ryong; Kang, Jin Gu; Kim, Miyoung; Braun, P. V.; Hwang, Sungwoo; Jung, Tae‐Sung
Abstract : There have been significant recent developments in the growth of single‐crystal gallium nitride (GaN) on unconventional templates for large‐area blue or green light‐emitting diodes (LEDs) which, together with layer transfer onto foreign substrates, can enable flexible and stretchable lighting applications. Here, the heteroepitaxial growth of GaN on amorphous and single‐crystal substrates employing various interlayers and nucleation layers is reviewed, as well as the use of weak interfaces for layer‐transfer onto foreign substrates. Recent progress in low‐temperature GaN‐based red–green–blue (RGB) LEDs on glass substrates, which has exhibited a calculated efficiency of 11% compared with that from commertial LEDs, is discussed. Layer‐transfer techniques with various interlayers are also discussed. These heteroepitaxial GaN growth and layer‐transfer technologies are expected to lead to new lighting and display devices with high efficiency and full‐color tunability, which are suitable for large‐area, stretchable display and lighting applications. Abstract : Recent progress in high‐quality GaN growth on unconventional templates and its transfer are reviewed. The main achievement includes GaN growth on 2D layered materials such as graphene and boron nitride, together with low‐temperature growth techniques and unusual transfer techniques. It is anticipated that such successful GaN‐based growth/transfer techniques will enable large‐area, flexible/stretchable, green/blue light‐emitting diodes.